Peran Pembina Agama Islam Dalam Meningkatkan Kualitas Keagamaan Bagi Wbp Wanita Dilapas Banyuwangi Kelas II A - Djamaludin, Winda Dewanti; Yohandi; Sulaiman, A. Husam (CV. SINAR HOWUHOWU, 2025)
This study aims to examine the efforts of Islamic religious mentors in enhancing the religious quality of female inmates, addressing weak faith as a key factor contributing to prohibited behaviors. Employing a qualitative approach, the research explores a series of religious guidance activities and identifies the factors that facilitate or hinder their implementation. The findings reveal that the efforts of Islamic religious mentors are carried out through: (a) regular religious study sessions; (b) performing the five daily prayers (Salat), either in congregation or individually; and (c) Qur’an reading and writing programs. Supporting factors are categorized as internal and external. Internal factors include: (a) adequate facilities and infrastructure, (b) strong teamwork among officers, and (c) collaboration with external institutions. External factors consist of: (a) the development of religious awareness among inmates and (b) motivational support from family members. Conversely, the hindering factors include internal issues such as (a) limitations in facilities and infrastructure, which require improvement, and (b) unplanned changes in the activity schedule. External obstacles include (a) low awareness and motivation among some inmates and (b) negative peer influence. To address these challenges, the study recommends: (a) ongoing enhancement of facilities and infrastructure, (b) fostering strong motivation and faith among inmates, and (c) reinforcing a structured and consistent activity schedule. Overall, Islamic religious guidance plays a significant role in supporting repentance and personal development, enabling female inmates to improve their quality of life.